Possibilities of corrosion assessment of metals in biodiesel using EIS - Calder, Jorge A.; Baena, Libia M.; Lenis, Julian (CT&F - Ciencia, Tecnología y Futuro, 2014)
Biodiesel is an alternative fuel obtained from renewable sources. However, during the biodiesel auto-oxidation, reactive compounds could be formed. Those compounds increase the biodiesel corrosivity and the degradation of the fuel. This work presents a study of the corrosion of metals commonly used in auto-parts exposed to biodiesel and biodiesel-fatty acids blends. Electrochemical Impedance Spectroscopy (EIS) measurements were performed during the exposition time in order to determine the susceptibility of the metals to corrosion. The polarization resistance (Rp) values at the initial exposition times were of the order of 1x109 ohm.cm2, and the associated capacitances were of the order of 10-11 F.cm-2 for all metals. The Nyquist impedance diagrams of copper and carbon steel -immersed in biodiesel-fatty acid blends after the second day of immersion- showed at least 2 capacitive loops. Although the capacitance values of lowest frequency loop are still too small (10-9 F.cm-2) to be associated with a metal double layer capacitance, the values of these capacitances increased with the increment of the exposition time. It is pos-sible that for longer times of exposition, the electrochemical parameter related with the lowest capacitive loop of the impedance can be associated to the metal corrosion phenomena.